2022
DOI: 10.3847/1538-4357/ac4ca6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Milky Way Circumgalactic Medium in a Cosmological Context with a Semianalytic Model

Abstract: We combine the Santa Cruz semianalytic model (SAM) for galaxy formation and evolution with the circumgalactic medium (CGM) model presented in Faerman et al. to explore the CGM properties of L * galaxies. We use the SAM to generate a sample of galaxies with halo masses similar to the Milky Way (MW) halo, M vir ≈ 1012 M ⊙, and find that the CGM mass and mean metallicity in the sample are correlated. We use the CGM masses and metallicities o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 120 publications
1
18
0
Order By: Relevance
“…Our constraints allow larger values of η for most of the cases in comparison to the isentropic model by Faerman et al (2020Faerman et al ( , 2022. In their recent work (Faerman et al 2022), they have considered three cases for their model: (1) with only thermal pressure, i.e., α = (P nth /P th ) + 1.0 = ((P CR + P B )/ P th ) + 1.0 = 1.1; (2) with the standard case as considered in Faerman et al (2020), i.e., α = 2.1; and (3) with significant nonthermal pressure where α = 2.9. Note that the abovementioned values of α are the values at the outer boundary and the profiles of α will follow a declining pattern as radius decreases (see the blue curve in the right panel of Figure 2 in Faerman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our constraints allow larger values of η for most of the cases in comparison to the isentropic model by Faerman et al (2020Faerman et al ( , 2022. In their recent work (Faerman et al 2022), they have considered three cases for their model: (1) with only thermal pressure, i.e., α = (P nth /P th ) + 1.0 = ((P CR + P B )/ P th ) + 1.0 = 1.1; (2) with the standard case as considered in Faerman et al (2020), i.e., α = 2.1; and (3) with significant nonthermal pressure where α = 2.9. Note that the abovementioned values of α are the values at the outer boundary and the profiles of α will follow a declining pattern as radius decreases (see the blue curve in the right panel of Figure 2 in Faerman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This diminished value of thermal pressure would also significantly change the abundance of high ionization species and thereby jeopardize the interpretation of their column densities. In a recent work by Faerman et al (2022), they modified their previous isentropic model (Faerman et al 2020) with significant nonthermal pressure (α = (P nth /P th ) + 1.0 = 2.9) and found that the gas temperature in the central region for the nonthermal model becomes lower than the value at which O VIII collisional ionization equilibrium temperature peaks, which in turn results in a lower O VIII column density. At low CGM masses, photoionization compensated for this effect by the formation of O VIII at larger radii, but for large gas masses and large mean densities (as in the MW), the photoionization effect is negligible and the total O VIII column density is low.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation fields can ionize and change the energy levels of ions, thus affecting which atomic transitions can emit or absorb photons. Previous works indicate that the presence of ionizing radiation fields can significantly modify the cooling and heating functions of gas (e.g., Wiersma et al 2009;Gnedin & Hollon 2012;Faerman et al 2022;Romero et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent simulation work that investigates the degree of hydrostatic equilibrium obtained by the CGM of Milky Way mass galaxies finds that there is a significant amount of nonthermal pressure support, such that a purely hydrostatic equilibrium model is not a good description of the halo gas (Oppenheimer 2018;Lochhaas et al 2020). Faerman et al (2022) applied the analytic model of Faerman et al (2020) to a semi-analytic model for galaxy formation and also found that non-thermal support was neces-sary to fit the observations. These recent works suggest that perhaps the hydrostatic hot halo model needs to be modified in order to describe the complexities of the observed and simulated CGM.…”
Section: Introductionmentioning
confidence: 99%